LINGUISTIC STRATEGY IN A CULINARY CONTEXT: PROCEDURE TEXT APPROACH TO TRADITIONAL FOOD AND CURRENT COOKING RECIPES - Dinda Cinta Amanda; Herlina; Dewi Kartikasari (Esteem Journal of English Education Study Programme, 2024)
The aim of this study is to discuss linguistic strategies in the context of procedure texts, highlighting the appropriate use of language to guide readers through the necessary steps. In this case we can find out the effectiveness of using linguistic strategies in the context of procedural texts in learning language comprehension for students at SMK Negeri 5 Palembang. The research methods used in this research were interviews and questionnaires. The research sample consisted of 29 students consisting of 15 male students and 14 female students. Data collection techniques were carried out using interviews and questionnaires. The results of this research indicate that linguistic strategies are effective for teaching understanding of procedural texts to class X students at SMK Negeri 5 Palembang.